Relativistic theory of the gravitation for Modified Newtonian Dynamics - Valenzuela, Mississippi (2023)
Modified Newtonian dynamics (MOND) is a hypothesis that proposes a modification of Newton's law of universal gravitation to account for observed properties of galaxies. This theory is an alternative to the hypothesis of dark matter in terms of explaining why galaxies do not appear to obey the currently understood laws of physics. In this work, we present a relativistic theory of gravitation for MOND.